2007
DOI: 10.1093/eurheartj/ehm328
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled study to evaluate the effect of two dosing regimens of darbepoetin alfa in patients with heart failure and anaemia

Abstract: In this study of patients with CHF and anaemia, treatment with darbepoetin alfa raised Hb using different dosing regimens. Darbepoetin alfa improved some quality of life indices, but its safety requires further exploration. Larger trials are needed to determine the effects on long-term morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 25 publications
3
159
0
5
Order By: Relevance
“…Several studies have focused on the effect of anemia correction, usually by iron and erythropoietin or darbopoietin, on exercise performance, measured either by peak _ VO 2 , exercise tolerance or by distance walked at the 6 min walking test, in both HF and non-HF patients [21][22][23][24][25][26][27][28][29]. However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the effect of anemia correction, usually by iron and erythropoietin or darbopoietin, on exercise performance, measured either by peak _ VO 2 , exercise tolerance or by distance walked at the 6 min walking test, in both HF and non-HF patients [21][22][23][24][25][26][27][28][29]. However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of 473 patients included in the Study of Anemia in Heart Failure-Heart Failure Trial [67] and another controlled trial of darbepoetin [68] showed a significantly lower risk for the combined endpoint of all-cause mortality or first heart failure-related hospitalization (HR, 0.67; confidence interval, 0.44 -1.03; p ϭ .06) in patients treated with the ESA rather than placebo [67,68]. In a recent meta-analysis of seven of these randomized trials of erythropoietic agents in CHF patients, including 363 treated patients and 287 controls, there was a significantly lower risk for CHF hospitalization (RR, 0.59; p ϭ .006) [69].…”
Section: The Effect Of Treating Anemia On Chfmentioning
confidence: 99%
“…In 2007, van Veldhuisen and colleagues reported a multi-centre, double-blind placebo-controlled trial in patients with NYHA class II-III CHF, a LVEF B40% and haemoglobin 9.0-12.5 g/dl using darbepoetin alfa as the active treatment [39]. Placebo (n = 55) or darbepoetin alfa was given subcutaneously every 2 weeks for 26 weeks at a starting weight adjusted dose of 0.75 mcg/kg (n = 56) or a fixed dose of 50 mcg (n = 54), to gradually achieve and maintain a target haemoglobin of 14.0 g/dl.…”
Section: Darbepoetin Alfa As a Treatment For Chfmentioning
confidence: 99%